Perubahan Sosial Masyarakat Akibat Perkebunan Kelapa Sawit di Desa Barambai Karya Tani Kabupaten Barito Kuala - Faqih, Ahmad; Khairussalam (Prodi Sosiologi FISIP ULM, 2024)
The life of the community in Barambai Karya Tani Village, Barito Kuala Regency depends on the agricultural sector, but in 2007 it began to be replaced by the entry of oil palm plantations owned by PT Agri Bumi Sentosa (ABS). This research aims to find out and describe the factors that encourage people to accept oil palm plantations, and examine the social changes caused by oil palm plantations. The research method used is qualitative, with a phenomenological research type. Data were collected using participant observation, semi-structured interviews and documentation. Data were analysed using an interactive model, which consists of data reduction, data presentation and conclusion drawing. The results showed that the factors that encourage people to accept oil palm plantations are: PT Agri Bumi Sentosa (ABS) has obtained the Cultivation Rights Title (HGU); the declining productivity of agricultural land; and the opening of jobs as permanent employees and daily labourers in oil palm plantation companies. The income earned, both as permanent employees and daily labourers, can meet the needs of daily life, so the existence of oil palm plantations can improve the community's economy. The negative side is that oil palm plantations cause interactions between communities to decline, as well as the erosion of the gotong-royong culture. It is expected for PT Agri Bumi Sentosa (ABS) to actively involve the community in every decision-making, so that the potential of oil palm plantations can be maximised in a sustainable manner and minimise the negative impacts caused.